Insect bite leading to a leg ulcer: a patient's story - Sylvie Hampton (British Journal of Community Nursing, 2026)
The patient, John, is a 94-year-old man with mild mobility issues but is otherwise fit and active. He developed a trauma-related ulcer, likely originating from an insect bite, that is now almost fully closed following treatment with compression hosiery. This case study discusses the symptoms, assessment, diagnosis, treatment plan and the outcomes resulting from timely and appropriate nursing interventions.